Thermal comfort and energy performance improvement by optimization of shading devices using improved Battle Royal algorithm. (23rd February 2023) - Hu, Guiqiu; Hu, Xiji; Pouramini, Somayeh
Summary: China's building energy consumption accounts for 27.5% of China's total energy demand. This amount is increasing because of the considerable increase in the rate of household equipment mostly in air‐conditioning systems. In this study, the TRNSYS simulation tool and improved Battle Royal optimizer (IBRO) is coupled for energy optimization of the building based on the simulation to study the impact of the overhangs optimization. The thermal comfort enhancement is evaluated in three case studies of three different weather conditions in China. To validate the achieved results, a comparison of the optimum values with benchmark cases is performed with consideration of heating and cooling demands, and yearly discomfort percentage. According to the achievements, an improvement can be seen in the comfort level. Also, the cooling demand is decreased by 4.2% for Shanghai.